Implementasi Total Productive Maintenance (TPM) dengan metode Overall Equipment Effectiveness (OEE) pada Mesin Threser di Koperasi KAREB - Budi Laksono, Galih; Eko Wahyu, Abryandoko (Jurnal Teknologi dan Manajemen Sistem Industri, 2023)
The advancement of technology encourages companies to enhance machine performance to support production. Routine maintenance ensures smoother operations and optimal machine utilization. However, suboptimal machine use reduces productivity and leads to production losses. One effective method to mitigate this is Total Productive Maintenance (TPM), with Overall Equipment Effectiveness (OEE) serving as a metric to evaluate productivity losses. Human error, often caused by fatigue, is a major source of downtime. Mechanical issues, such as conveyor belt damage from sugar tobacco residue, and environmental factors like high temperatures or electrical disturbances, also contribute to machine inefficiency. In the thresher unit of the KAREB Cooperative, several disruptions affect machine effectiveness. OEE analysis in May 2022 showed a value of 11.81%, far below world-class standards, primarily due to significant machine damage during that period. While the defect rate was 0%, the highest downtime occurred in week 3, when intensive production caused frequent machine issues.